Gut microbiota, immune cell, colorectal cancer association mediators: a Mendelian randomization study - Yuegang Li; Meng Zhuang; Shiwen Mei; Gang Hu; Jinzhu Zhang; Wenlong Qiu; Xishan Wang; Jianqiang Tang (BMC Cancer)
Abstract Background There have been previously reported associations between the gut microbiota, immune cells, and colorectal cancer; however, the specific mechanisms underlying these relationships remain largely unexplored and require further research. Therefore, in this study, we aimed to unravel the interactions between the gut microbiota, immune cells, and colorectal cancer. Methods The analysis used genome-wide association study (GWAS) data encompassing 207 microbial taxa and 205 functional pathways and data on 731 immune cell phenotypes. Colorectal cancer data on 6 581 cases and 463 421 controls were sourced from the Integrative Epidemiology Unit Open GWAS Project. Univariate inverse-variance weighted Mendelian randomization analysis was used to identify gut microbial taxa associated with colorectal cancer. Mediation analysis was used to identify the mediating role of specific immune cells in the link between gut bacteria and colorectal cancer. Results Univariate inverse-variance weighted Mendelian randomization analysis revealed that several microbial taxa from the Actinobacteria and Firmicutes phyla were significantly associated with colorectal cancer. Coriobacteriaceae (odds ratio [OR]: 0.84, 95% confidence interval [CI]: 0.72–0.97), Sutterellaceae (OR: 0.88, 95% CI: 0.78–0.99), Eggerthella (OR: 0.91, 95% CI: 0.84–0.99), Coriobacteriales (OR: 0.84, 95% CI: 0.72–0.97), Collinsella aerofaciens (OR: 0.85, 95% CI: 0.74–0.99), and Ruminococcus bromii (OR: 0.91, 95% CI: 0.83–0.99) were negatively associated with colorectal cancer, whereas Lactobacillales (OR: 1.11, 95% CI: 1.03–1.20), Veillonella (OR: 1.08, 95% CI: 1.01–1.15), and Bifidobacterium bifidum (OR: 1.05, 95% CI: 1.00–1.09) were positively associated with colorectal cancer. Mediation analysis revealed that in the causal pathway from Collinsella aerofaciens to colorectal cancer, CD127 on CD28+ CD45RA− CD8br and human leukocyte antigen (HLA) DR on CD33− HLA DR+, mediated 11.30% and − 6.52% of the effect, respectively, and that in the causal pathway from Ruminococcus bromii to colorectal cancer, IgD− CD38dim %lymphocyte mediated − 14.80% of the effect. Conclusions These results highlight the potential of gut microbiota and immune cell phenotypes as novel treatment strategies for colorectal cancer.